(untitled) (Global Journal of Human-Social Science, 2017)
Globalization of economic processes requires an adequate transformation of the economic Sciences. In the modern world the globalization of factors and results of production leads to the formation of global relations of ownership and governance. It modifies the subject field of General economic theory, and generates the global political economy. The essence of its subject is the relationship of the global ownership and the resulting global economic contradictions. The methodological toolkit of global political economy reflects the particularities of contemporary scientific knowledge due to the new phenomena of globalization. Global political economy is the methodological-theoretical basis of all Sciences, studying global economic system. At the same time it is a special branch of the modern system of economic Sciences, characterizing by the spatio-temporal specificity of subject and method.